Racial disparities in prostate cancer: A complex interplay between socioeconomic inequities and genomics. (10th April 2022) - Lowder, Dallin; Rizwan, Kinza; McColl, Collin; Paparella, Alyssa; Ittmann, Michael; Mitsiades, Nicholas; Kaochar, Salma
Abstract: The largest US cancer health disparity exists in prostate cancer, with Black men having more than a two-fold increased risk of dying from prostate cancer compared to all other races. This disparity is a result of a complex network of factors including socioeconomic status (SES), environmental exposures, and genetics/biology. Inequity in the US healthcare system has emerged as a major driver of disparity in prostate cancer outcomes and has raised concerns that the actual incidence rates may be higher than current estimates. However, emerging studies argue that equalizing healthcare access will not fully eliminate racial health disparities and highlight the important role of biology. Significant differences have been observed in prostate cancer biology between ancestral groups that may contribute to prostate cancer health disparities. Notably, relative to White men, Black men with prostate cancer exhibit increased androgen receptor signaling, genomic instability, metabolic dysregulation, and inflammatory and cytokine signaling. Immediate actions are needed to increase multi-center, interdisciplinary research to bridge the gap between social and biological determinants of prostate cancer health disparities. Highlights: Black men are 2.14 times more likely to die from prostate cancer compared to White men. Equalizing access-to-quality-care is unlikely to fully eliminate racial health disparities. Significant differences have been observed in prostate cancer biology among various ancestral groups. Interdisciplinary research is needed to bridge the gap between social and biological factors. Increasing racial diversity in preclinical models and clinical trials is critically needed.